(untitled) (American Journal of Islam and Society, 1995)
The International Islamic Calendar Programme relies on calculations of the new moon’s expected visibility. The term "new moon’s visibility" gives a wrong connotation, because the astronomical term "new moon" refers to a moon that is completely dark and invisible. Therefore, from here on the term "crescent moon" or simply "crescent" will be used for a moon that could be visible after the new moon phase. The problem of predicting the crescent moon’s visibility has been of interest to astronomers in general for a friendly competition of sighting a young crescent moon and to Muslims for their needs associated with the Islamic calendar. The earliest astronomical criterion for visibility appeared in the Babylonian era: the moon’s age after conjunction must be more than 24 hours, an arc of separation as must be more than 12° or the moon sets 48 minutes after sunset. Hindus (500-700 C.E.) developed a more elaborate system of calculations with the same as >= 12° criterion. In the eighth to tenth centuries C.E., Muslim astronomers, notably Ya’qub ibn Tariq, Habash, al Khwarizmi, al Farghani, and al Battani excelled in mathematical astronomy and developed rules for predicting the crescent’s visibility based on the importance of the crescent’s width. A century later, al Biruni recommended al Battani’s procedures. In the fifth century, al Sufi and al Kashani still quoted the early Babylonian criterion of as >=12° . In the late part of the nineteenth century, Schmidt recorded observations in Athens, Greece, throughout a period of twenty years. Fotheringham (1910) and Maunder (1911), who used Schmidt’s data and then added some more observational data, made the first significant developments in criterion for visibility since the time of al Battani. Bruin (1977) developed an independent physics-based criterion involving such variables as the sky’s brightness, contrast, the crescent’s intensity, and so on. However, his criterion was only theoretical and its validity needed to be proven by actual observations. Ilyas (1981) modified Bruin’s criterion in order to remove the discrepancy in his method and the actual observational criterion of Maunder. All of these suggested criteria for calculating expected visibility have been summarized in a tabular form on page 15 ...